2018
DOI: 10.1212/wnl.0000000000005216
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency oscillations in awake patients undergoing brain tumor-related epilepsy surgery

Abstract: HFOs are common in brain tumor-related epilepsy, and HFO rate may be a useful measure of epileptogenicity in gliomas. Our findings further support the notion that IDH1 mutant genotype is more epileptogenic than IDH1 wild-type genotype gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 26 publications
3
36
0
1
Order By: Relevance
“…One might hypothesize that more affected tissue will produce more pathological signals. One study found higher rates of HFOs in patients with IDH1 mutant tumors 20 . Our cohort only included one patient with an IDH1 mutant tumor, who showed both ripples and fast ripples but not at particularly high rates.…”
Section: Discussionmentioning
confidence: 99%
“…One might hypothesize that more affected tissue will produce more pathological signals. One study found higher rates of HFOs in patients with IDH1 mutant tumors 20 . Our cohort only included one patient with an IDH1 mutant tumor, who showed both ripples and fast ripples but not at particularly high rates.…”
Section: Discussionmentioning
confidence: 99%
“…Feyissa ve ark. [15] 2018'de yayınladıkları çalışmada; IDHmutant genotipin, IDH-wild (negatif ) genotip gliomlardan daha epileptojenik olduğunu savunmuşlardır. Literatürle uyumlu olarak; bazal ganglia ve insula yerleşimli tümörlerde ameliyat öncesi ve sonrası dönemde epileptik nöbet görülme insidansı, kortikal yerleşimli tümörlere göre daha az saptanmıştır.…”
Section: Discussionunclassified
“…Tumors involving the cerebral cortex, particularly the motor cortex, are more likely to produce seizures than tumors in the deep gray matter, although the latter can also lead to seizures because of surrounding edema and mass effect . Seizures can be a significant source of quality‐of‐life impairment for patients with brain tumors …”
Section: Seizures In Patients Who Have Cancer With Brain Lesionsmentioning
confidence: 99%
“…11 Seizures can be a significant source of quality-of-life impairment for patients with brain tumors. [12][13][14][15] In addition to the brain lesions themselves, seizures can also be a byproduct of the treatment provided, including surgery, radiation, and systemic therapies. On the basis of retrospective analyses of neurosurgical records, the estimated incidence of seizures after craniotomy is between 15% and 20%.…”
Section: Seizures In Patients Who Have Cancer With Brain Lesionsmentioning
confidence: 99%